1991
DOI: 10.1159/000247752
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Biophysical Characterization of Skin Physiological Differences in Races

Abstract: The role of race in modulating skin responses has been investigated. Several parameters (skin thickness, transepidermal water loss, water content of the stratum corneum and skin biomechanics) have been measured using noninvasive tools in whites, Hispanics and blacks to assess whether the melanin content could induce changes in skin biophysical properties. Marked differences between races appear in stratum corneum water content and in skin extensibility, recovery and elastic modulus. Measurements done in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(92 citation statements)
references
References 5 publications
(7 reference statements)
2
79
2
1
Order By: Relevance
“…Weigand et al [5] suggested a higher stratum corneum lipid content in black skin, whereas Hellemans et al [6] reported similar stratum corneum ceramide levels in Asians and Caucasians with lower levels in Africans. Similar inconsistencies were, among others, also found for the stratum corneum barrier function [7,8], the stratum corneum water content [4,9] and skin resistance to chemical irritation [10,11]. …”
Section: Introductionsupporting
confidence: 73%
“…Weigand et al [5] suggested a higher stratum corneum lipid content in black skin, whereas Hellemans et al [6] reported similar stratum corneum ceramide levels in Asians and Caucasians with lower levels in Africans. Similar inconsistencies were, among others, also found for the stratum corneum barrier function [7,8], the stratum corneum water content [4,9] and skin resistance to chemical irritation [10,11]. …”
Section: Introductionsupporting
confidence: 73%
“…Others have reported the opposite on larger numbers of individuals, e.g. Berardesca et al [41] reported no differences between subjects of Negroid, Caucasian and Hispanic descent. Sugino et al [40] reported that TEWL was greater in the order: Blacks > Caucasians > Hispanic > Asian.…”
Section: Stratum Corneum Barrier Functionmentioning
confidence: 94%
“…This is consistent with a thicker stratum corneum for Negroids and a thinner stratum corneum for Asians. Berardesca et al [41,47], for instance, observed no racial differences in TEWL on either the volar or dorsal forearms. Skin surface temperature differences can contribute to the differences in TEWL.…”
Section: Stratum Corneum Barrier Functionmentioning
confidence: 99%
“…Volar and dorsal forearms present a significant differences between all races. 15 These results are apparently contrast with TEWL recordings. Indeed, increased SC water content, correlates with a higher TEWL.…”
Section: Question 2: Do the Biophysical Properties Of Asian Skin Diffmentioning
confidence: 82%